Relationship Between Personality Traits and Emotion Regulation Among Adolescent Athletes - R. Karmakar; A. Ghosh (Moscow State University of Psychology and Education, 2023)
Emotions are inevitable in our day-to-day life and play most important role in maintaining interpersonal relationship, communication, and overall quality of life. The ability to regulate emotion is also very important to deal effectively with everyday life stressors. Personality is an important aspect of human being and determines the unique adjustment of human being with his/her environment. Personality traits also influence the perception of an individual and thereby impact the way an individual regulates his/her emotions. Emotion regulation varies significantly across individuals so as the personality traits. The present study aims at determining the relationship between personality traits and emotion regulation among athletes and non-athletes. The present cross- sectional study was conducted on participants (N=180), consisting of athletes (N=80; Male= 55 and Female= 25) and non-athletes (N= 100; Male= 45 and Female= 55). All participants were selected through convenient sampling method. Pearson’s product moment correlation of coefficient reveals that for athletes Openness to experience and extraversion are significantly and positively correlated to cognitive reappraisal and neuroticism is significantly and positively correlated to expressive suppression. This means that athletes high on openness to experience and extraversion tend to use cognitive appraisal as an emotion regulation strategy whereas athletes high on neuroticism tend to prefer suppression strategy. For non-athletes, openness to experience, conscientiousness are significantly and positively correlated to cognitive reappraisal and neuroticism is significantly and positively related to suppression. This suggests that individuals high on openness to experience and conscientiousness are also high on cognitive appraisal and those who are high on neuroticism are also high suppression. Multiple regression analyses suggest for athletes, openness to experience and neuroticism are the significant predictors of Cognitive reappraisal and neuroticism is the most significant predictor of expressive suppression. For non-athletes, conscientiousness and openness to experience are the significant predictors of Cognitive reappraisal. and neuroticism is the most significant predictor of expressive suppression. The study discusses the pertinent potential implications of results.